Late adoption: the child's adaptation process from the point of view of adoptive parents (Research, Society and Development, 2022)
Late adoption refers to the process of adopting children over two years of age. It is complex and has challenges for parents and children due to the past history, trauma and learning that accompany this child. This process guarantees the child access to rights, basic physical and psychological needs, and the couple the possibility of playing the role of parents. The aim of this study was to investigate the children's adaptation and the coping strategies that were experienced in the late adoption process from the point of view of the adoptive parents. Five families participated in the semi-structured interview composed of themes that investigated the experiences of the adoption process. Data analysis was performed using categorical analysis and the results were divided into five categories: (1) adaptation process after adoption, (2) changes in family routine, (3) difficulties in the child's adaptation, (4) behaviors perceived by parents and (5) emotional adaptation. The results showed that at the beginning of the adoption, the children rejected their parents given the history of neglect and trauma that triggered psychological and emotional issues that influenced this process. Establishing a bond, adapting the child to the new routine, adapting behaviors and emotional issues were cited as challenges of the first periods of family life. The research revealed the importance of the family being accompanied by a multidisciplinary team in order to learn to deal with the challenges of the child's adaptation in the new home. New studies must be conducted to understand how psychology can help in these cases.